2021
DOI: 10.1111/pere.12394
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Polish‐Language Relationship Disillusionment Scale and its validation

Abstract: In Poland, individuals enter marriages and relationships increasingly to derive personal fulfillment, creating high expectations that may elevate individuals' risk for romantic disillusionment (the perception that the relationship has not lived up to expectations and has deteriorated). Given these dynamics in Poland, a Polish‐language measure of disillusionment would open up new research opportunities. Three studies, therefore, examined psychometric properties of a new Polish‐Language Relationship Disillusionm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Our investigation extended these prior studies by showing how single individuals, regardless of being a current, former, or never-user, position themselves in regard to the dating technology that is available in Polish society characterized by the increasing prevalence and acceptance of dating technology (Marganski, 2017;Rychłowska-Niesporek, 2019) and a strong adherence to the ideology of coupledom and marriage (Janicka and Szymczak, 2019; Niehuis et al, 2021) in conjunction with the low acceptance rate of singlehood (CBOS, 2019).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our investigation extended these prior studies by showing how single individuals, regardless of being a current, former, or never-user, position themselves in regard to the dating technology that is available in Polish society characterized by the increasing prevalence and acceptance of dating technology (Marganski, 2017;Rychłowska-Niesporek, 2019) and a strong adherence to the ideology of coupledom and marriage (Janicka and Szymczak, 2019; Niehuis et al, 2021) in conjunction with the low acceptance rate of singlehood (CBOS, 2019).…”
Section: Discussionsupporting
confidence: 64%
“…Second, in general, Poland is characterized by a strong adherence to heterosexual marriage, general disapproval and low incidence rates of divorce, and less approval for alternative marital life formats (Janicka and Szymczak, 2019). Therefore, Poland may be considered a society that highly endorses the ideology of marriage and family and is strongly oriented toward coupledom (Niehuis et al, 2021); this is reflected in the Polish census data, which demonstrates that 45% of Poles express unfavorable attitudes toward singlehood (Centre for Public Opinion Research (CBOS), 2019). As a result, the Polish context appears to have a strong potential to affect the phenomenon of singlehood, thereby contributing to a negative perception of single individuals as being those who do not follow the socially accepted life path, that is, being in a serious relationship, in particular a marital relationship (Janicka and Szymczak, 2019).…”
mentioning
confidence: 99%
“…• • The single-item and full-length measures of relationship satisfaction were tested for (negative) correlation with the criterion of romantic disillusionment (Niehuis et al, 2019(Niehuis et al, , 2021. Disillusionment has been conceptualized, in part, in terms of perceived declining satisfaction (Huston et al, 2001;Niehuis et al, 2011) and has been related empirically to self-perceived declines in favorable relationship qualities (Niehuis & Bartell, 2006).…”
Section: The Present Researchmentioning
confidence: 99%
“…In turn, Pereira et al (2014) noted the lack of a link between prayer for a partner and loneliness. With respect to marital/relationship disillusionment, this factor has been recognized in the literature as one of the factors related to stability vs. termination of marital and other relationships (Niehuis et al 2021) that is defined as "an extreme version of disappointment [that] captures individuals' perception that their relationship has changed for the worse" (Niehuis et al 2019, p. 210). In past research, greater disillusionment in cohabiting and married couples has been found to be related to a higher self-rated likelihood of relationship termination, even when relationship satisfaction, commitment, and length were controlled (Niehuis et al 2015), and actor and partner effects of disillusionment temporally preceded individuals' depressive symptoms (see Niehuis et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to marital/relationship disillusionment, this factor has been recognized in the literature as one of the factors related to stability vs. termination of marital and other relationships (Niehuis et al 2021) that is defined as "an extreme version of disappointment [that] captures individuals' perception that their relationship has changed for the worse" (Niehuis et al 2019, p. 210). In past research, greater disillusionment in cohabiting and married couples has been found to be related to a higher self-rated likelihood of relationship termination, even when relationship satisfaction, commitment, and length were controlled (Niehuis et al 2015), and actor and partner effects of disillusionment temporally preceded individuals' depressive symptoms (see Niehuis et al 2021). Because prior studies have well documented the link between marital/relationship disillusionment and several relationship outcomes, the inclusion of this construct that has not been-to the best of our knowledge-examined in research on praying and relationship outcomes appears to be an important task in this area.…”
Section: Introductionmentioning
confidence: 99%